A Micro-Analytic Model of the Generation and Application of Savings in Small Business - Korbel, John (The Review of Economics and Statistics, 1965)
T HE importance of retained earnings as a source of funds for financing corporate growth has been widely recognized. Also well recognized is the considerable short-run variability of corporate saving. Accordingly, there have been a number of studies of the policies and behavior of corporations with respect to income retention. Most of these (1) have been concerned with large corporations and (2) have relied upon aggregative time-series data and/or cross-sectional data.' This study is concerned